Physical and Biochemical Studies in Jack's Semen - Gupta, A K; Singh, R; Mamta, Mamta; Singh, M K; Singh, M K; Pal, Yash (Annals of Arid Zone, 2016)
Semen samples of five French donkeys (Poitu breed) maintained at cryopreservation laboratory were evaluated at different intervals during both breeding and non-breeding seasons, for their physical and biochemical parameters, to assess their individual potential and further use for cryopreservation. Samples were collected using artificial vagina at weekly interval throughout the year. Semen was creamy to '01'1' white' in color and of thin to thick consistency in all the jacks during period of the study. Semen volume was significantly higher during non-breeding season as compared to breeding season, while reverse was true for live sperm per cent, initial motility, progressive motility and sperm concentrations. A significant positive correlation was observed among spermatozoa concentration. live sperm per cent. initial motility and progressive motility and all these were negatively correlated with semen volume. Among biochemical parameters including different enzymes, metabolites and ions, significant differences in their values during breeding and non-breeding seasons, as well as among indi-.;iduals were observed. Activity of SDH enzyme remained almost constant throughout the study indicating that fructose may not be the direct source of energy for spermatozoa. Among all the jacks. the quality of two jacks was appreciably better than the rest. Overall semen quality was better duri ng breedi ng season than non-breedi ng season. Key words: Jacks, seminal plasma, semen, seasons, physical, biochemical.